The quality of relationships and the ability of Civil Service of Call Center Customer Satisfaction in PT 123. PLN (Persero) Central Java Distribution & D.I. Yogyakarta - Restuari Hildawati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2012)
As a company that organizes services, PT. PLN (Persero) Central Java Distribution & D.I. Yogyakarta is still not optimal in organizing the 123 Call Center services. In this study the authors observed 123 Call Center customer satisfaction is submitting the complaint to determine whether there is a relationship between the factors of service quality and the ability to work to the satisfaction of service in PT 123 Call Center. PLN (Persero) Central Java Distribution & D.I. Yogyakarta.Type of study is a research type ekspalanatori. This study used a sample of 50 respondents to the selection of accidental sampling technique. Analysis of data using quantitative methods. Testing the hypothesis using Rank Correlation Coefficient formula and formula Kendal Kendall Coefficient of Concordance.According to the results showed a significant relationship between the variable quality of service (X1) with customer satisfaction (Y) where the value Zcalc > Ztable 5% (6.72 > 1.96), a significant relationship between employee capability variable (X2) with customer satisfaction (Y) where the value Zcalc > Ztable 5% (5.38 > 1.96), and a significant relationship between quality of service (X1) and the ability of employees (X2) to customer satisfaction (Y) where the value calculated ƒÓ 2 > ƒÓ 2 tables on a significant level of 5%, which is 33.644 > 5.991. Based on the results showed that the quality of service and the ability of employees to have a relationship with customer satisfaction on PT. PLN (Persero) Central Java Distribution & D.I. Yogyakarta.